Entrepreneurial Interest among Higher Education Students: The Role of Emotional Intelligence, Entrepreneurship Education, and Entrepreneurial Motivation - Sandi Sandi; Sahiruddin Sahiruddin; Yusuf Yusuf; Adam Rahman Suradi; Achmad Dahlan Abdullah (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study aims to examine the influence of emotional intelligence and entrepreneurship education on entrepreneurial interest through entrepreneurial motivation in the higher education context. A quantitative approach was employed using a survey design. The population consisted of 546 students, from which 107 respondents were selected through simple random sampling. Data were collected using a questionnaire that had been tested for validity and reliability. The data were analyzed using Structural Equation Modeling to assess the direct and indirect relationships among variables. The findings show that emotional intelligence and entrepreneurship education have a significant effect on entrepreneurial motivation. Entrepreneurial motivation also plays a significant mediating role in the relationship between emotional intelligence and entrepreneurship education on entrepreneurial interest. These results indicate that strengthening students’ emotional intelligence and improving the quality of entrepreneurship education can enhance entrepreneurial interest, particularly when supported by strong entrepreneurial motivation. The study provides practical implications for the development of entrepreneurship curricula and educational programs that are capable of fostering a more entrepreneurial mindset among students in higher education.